Peran Moderasi Literasi Keuangan dalam Hubungan Modal Intelektual Hijau, Keunggulan Kompetitif Hijau, dan Kinerja Keuangan UMKM - Jayanti Mandasari; Serli Oktapiani (Politeknik Ganesha Medan, 2025)
This research’s main objective is to improve the financial performance (FP) of MSMEs by improving the implementation of strategies based on Green Competitive Advantage (GCA) and GIC (Green Intellectual Capital) through financial literacy (FL). The development of MSMEs aligns with environmental sustainability. The high level of productivity, potential, and compatibility with environmental improvement made Sumbawa Regency, NTB, the study's choice. utilizing interview and survey methods to gather data and descriptive methods. Purposive sampling was employed to select respondents from a sample of 300. The study concludes that Green Intellectual Capital (GIC) and Green Competitive Advantage (GCA) exert a significant influence on the financial performance (FP) of micro, small, and medium enterprises (MSMEs). Furthermore, Financial Literacy (FL) functions as a moderating variable that strengthens the relationship between both GIC and GCA with MSMEs’ financial performance. The strategies, concepts, formulation patterns, and actions for adapting knowledge that support community and MSMEs’ independence include, in particular, highly qualified human resources, superior competencies based on knowledge innovation, and synergistic business competition in environmental protection with sound financial literacy. supporting ecosystem development plans and policies for long-term, continuous business growth.